Association of serum N-terminal pro-brain natriuretic peptide levels with survival and renal outcomes among elderly patients with acute kidney injury in chronic heart failure - Hou, Jiebin; Zhang, Xin; Wu, Zhen; Liu, Yang; Zhang, Yabin; Zhao, Jiahui; Wang, Xiaohua; Chen, Hongyu; Yang, Guang; Ma, Qiang; Cheng, Qingli; Ao, Qiangguo (Frontiers in Cardiovascular Medicine, 2023)
Background: Elderly patients exhibit a higher incidence of chronic heart failure (CHF). Patients with CHF can develop acute kidney injury (AKI) during follow-up, which can result in poor prognosis. This relationship between kidney dysfunction and levels of N-terminal pro-brain natriuretic peptides (NT-proBNP), with regard to prognosis, is complicated and has rarely been analyzed in elderly patients with CHF. Method: We conducted a retrospective cohort study involving patients with a CHF history aged ≥ 65 years, who experienced an episode of AKI. Kaplan–Meier curves and Cox or logistic proportional hazards regression models were used to evaluate the association between serum NT-proBNP concentrations and mortality or renal recovery by day 90. Results: A total of 1160 eligible patients with AKI were available for the study. Of this sample, 41.5% of patients died within 90 days of the onset of AKI. Patients with a decreased change in NT-proBNP accompanying the episode of AKI had a lower risk (adjusted OR= 0.56, 95% CI=0.34-0.91) of more severe AKI (stage 2 and 3 vs. stage 1). The more severe AKI were associated with higher mortality and non-recovery of renal function in elderly patients with CHF, independent of NT-proBNP levels. Elevated levels of baseline lnNT-proBNP (adjusted HR = 1.27, 95% CI = 1.17-1.38) predicted mortality in elderly patients with CHF within 90 days of AKI onset. Patients with a decrease in NT-proBNP accompanying AKI had a lower risk of mortality (adjusted HR = 0.62, 95% CI = 0.48-0.79). However, a decrease in NT-proBNP is a risk factor (adjusted OR= 1.59, 95% CI=1.02-2.48) for the non-recovery of renal function following AKI—especially in elderly survivors with low baseline NT-proBNP levels. Conclusion: A decreased change in NT-proBNP maybe protective for elderly patients with CHF by improving survival outcomes and preventing severe AKI. However, an excessive decrease in BNP is a risk factor for the non-recovery of renal function following AKI. Avoiding excessive changes in NT-proBNP may be protective for survival and renal injury prognosis.